Deglaciation of the Greenland and Laurentide ice sheets interrupted by glacier advance during abrupt coolings. (1st February 2020) - Young, Nicolás E.; Briner, Jason P.; Miller, Gifford H.; Lesnek, Alia J.; Crump, Sarah E.; Thomas, Elizabeth K.; Pendleton, Simon L.; Cuzzone, Joshua; Lamp, Jennifer; Zimmerman, Susan; Caffee, Marc; Schaefer, Joerg M.
Abstract: Understanding patterns of ice-sheet deglaciation is key for predicting the rate of future ice-sheet melt, yet the processes underlying deglaciation remain elusive. The early Holocene (11.7 ka to 8.2 ka; Greenlandian Stage) represents the most recent period when the Laurentide and Greenland ice sheets underwent large-scale recession. Moreover, this ice-sheet recession occurred under the backdrop of regional temperatures that were similar to or warmer than today, and comparable to those projected for the upcoming centuries. Reconstructing Laurentide and Greenland ice sheet behavior during the early Holocene, and elucidating the mechanisms dictating this behavior may serve as a partial analog for future Greenland ice-sheet change in a warming world. Here, we present 123 new 10 Be surface exposure ages from two sites on Baffin Island and southwestern Greenland that constrain the behavior of the Laurentide and Greenland ice sheets, and an independent alpine glacier during the early Holocene. On Baffin Island, we focus on a unique area where moraines deposited by the Laurentide Ice Sheet rest directly adjacent to moraines deposited by an independent alpine glacier. Sixty-one 10 Be ages reveal that advances and/or stillstands of the Laurentide Ice Sheet and an alpine glacier occurred in unison around 11.8 ka, 10.3 ka, and 9.2 ka. Sixty-two 10 Be ages from southwestern Greenland indicate that the Greenland Ice Sheet margin experienced re-advances or stillstands around 11.6 ka, 10.4 ka, 9.1 ka, 8.1 ka, and 7.3 ka. Our results reveal that ice sheets respond to climate perturbations on the same centennial timescale as small alpine glaciers. We hypothesize that during the warming climate of the early Holocene, freshening of the North Atlantic Ocean induced by ice-sheet melt resulted in regional cooling and brief periods of ice-sheet stabilization superimposed on net glacier recession. These observations point to a negative feedback mechanism inherent to melting ice sheets in the Baffin Bay region that slows ice-sheet recession during intervals of otherwise rapid deglaciation.